Analisis Makna Onomatope dalam anime BangDream Season 1 Karya Nakamura Kou - Aisyah Annurillah Wahyu Putri; Putu Dewi Merlyna Yuda Pramesti; Yeni Yeni (STKIP AGAMA HINDU SINGARAJA, 2023)
This research aims to analyze onomatopoeia in ANIME BANGDREAM SEASON 1. This research is a linguistic research using descriptive qualitative method. The theory used is semantic theory. The data collection method used is the listening method and note-taking technique, the data used is anime. Then to prove the validity of the data, the triangulation method was used. The onomatopoeia data found is divided into 3 types. Gitai-go onomatopoeia was found in 2 sentences, Gijou-go onomatopoeia was found in 6 sentences, Giyou-go onomatopoeia was found in 2 sentences. The most widely used onomatopoeia in the anime is gijou-go onomatopoeia which has the characteristics of describing psychological states or human feelings, while gitai-go and giyou-go onomatopoeia are very rarely found in their unique use.